Satellite DNA methylation status and expression of selected genes in Bos indicus blastocysts produced in vivo and in vitro. Issue 2 (31st January 2017) - Urrego, R.; Bernal-Ulloa, S.M.; Chavarría, N.A.; Herrera-Puerta, E.; Lucas-Hahn, A.; Herrmann, D.; Winkler, S.; Pache, D.; Niemann, H.; Rodriguez-Osorio, N.
Summary: Bovine embryos produced in vivo and in vitro differ with respect to molecular profiles, including epigenetic marks and gene expression profiles. This study investigated the CpG methylation status in bovine testis satellite I (BTS) and Bos taurus alpha satellite I (BTαS) DNA sequences, and concomitantly the relative abundance of transcripts, critically involved in DNA methylation (DNMT1 and DNMT3A), growth and development (IGF2R) and pluripotency (POU5F1) in Bos indicus embryos produced in vitro or in vivo . Results revealed that methylation of BTS were higher ( P < 0.05) in embryos produced in vitro compared with their in vivo produced counterparts, while the methylation status of BTαS was similar in both groups. There were no significant differences in transcript abundance for DNMT3A, IGF2R and POU5F1 between blastocysts produced in vivo and in vitro . However, a significantly lower amount of DNMT1 transcripts was found in the in vitro cultured embryos ( P < 0.05) compared with their in vivo derived counterparts. In conclusion, this study reported only minor changes in the expression of developmentally important genes and satellite DNA methylation related to the in vitro embryo production system.